The Role Of Leadership Style In Fostering Creativity In The Workplace - Hardiani; Muhammad Tafsir (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The success of a business in the face of competition is inextricably linked to the ability of a transformational leader to foster a climate of creativity in the workplace. This study presents the findings of an analysis of the role of transformational leaders in fostering a climate of creativity in organizations. Multiple regression analysis is used to analyze data collected from respondents who are randomly selected from employees at several companies and then processed using the SmartPLS application. The researcher developed an instrument for the variables transformational leadership and climate of creativity based on several instruments used in previous research. The findings indicate that there is a strong correlation between transformational leadership and a climate of creativity, implying that transformational leadership plays a critical role in fostering creativity in the workplace.